Social Engineering and Legal Framework for Drug Rehabilitation: A Comparative Analysis of National Legislation in Indonesia - Ngaisah, Siti; Widoyoko, Wredha Danang; Haryono, Haryono; Rahmawati, Diah Ayu; Prayogi, Yoga Adi (Westscience Press, 2024)
Drug addiction poses a significant challenge to public health, social stability, and legal systems worldwide. This study examines Indonesia’s legal framework for drug rehabilitation through a juridical analysis and compares it with international best practices, focusing on Portugal and Switzerland. Findings reveal that while Indonesia’s Law No. 35 of 2009 on Narcotics incorporates rehabilitation, implementation gaps, inconsistent legal applications, and societal stigma hinder its effectiveness. Comparative analysis highlights the success of health-centered approaches and community-based programs in other countries. This paper underscores the importance of legal reforms, socio-cultural adaptability, and social engineering in enhancing drug rehabilitation policies in Indonesia. Recommendations include clearer legal guidelines, enhanced rehabilitation infrastructure, and public awareness initiatives to foster systemic change.